Relationship between HbA1c and Steroid in Initial Attack of Idiopathic Nephrotic Syndrome in Children - Naher, Nurun; Sultana, Sabina; Matin, Abdul (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Blood sugar may be raised as a systemic effect of steroid. Haemoglobin A1c (HbA1c) estimation provides an accurate index of mean concentration of blood glucose during preceding two to three months. Objective: The purpose of the present study was to observe the relationship between oral prednisolone and HbA1c levels in children with 1st attack Nephrotic syndrome. Methods: This case-control study was conducted in the Outpatient department of Apollo Hospitals, Dhaka, Bangladesh from January 2012 to July 2013 for a period of nineteenth (19) months. The nephrotic children with first attack who completed 12 weeks steroid therapy were enrolled as study group. Age and sex matched thirty children with other illness without family history of diabetes regarded as control. HbA1c level was estimated in Nephrotic patient just at the end of their 12 weeks of prednisolone therapy. Results: The mean age of study and control group was 4.56±1.54 and 4.90±1.06 years respectively. Male and female ratios were 1.0:0.76 and 1.0:0.88 in case and control group respectively. Age and sex difference between the groups were not significant. The mean HbA1c value was 5.00±0.28 in case and 4.43±0.35 in control group (p<0.0001). The calculated mean blood sugar level was 99.75±9.80 mg/dl and 80.30±12.48 mg/dl in case and control group respectively (p<0.0001). Conclusion: Nephrotic child getting steroid have significantly higher level of HbA1c then their healthy counterpart though the level is not at diabetic level. Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 7-9